2013
DOI: 10.5694/mja12.11699
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral intravenous catheter‐associated Staphylococcus aureus bacteraemia: more than 5 years of prospective data from two tertiary health services

Abstract: PIVC-associated SAB is an under-recognised complication. The high incidences of SAB associated with PIVCs inserted in emergency locations and with prolonged dwell times support recommendations in clinical guidelines for routine removal of PIVCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
90
2
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(99 citation statements)
references
References 11 publications
2
90
2
5
Order By: Relevance
“…La flebitis asociada a los dispositivos venosos causa infección nosocomial, lo que puede suponer una prolongación de la estancia hospitalaria e incluso complicarse con una sepsis, aunque la incidencia es baja (10) . En la mayoría de los casos se trata de infección por Estafilococo Aureus que puede desembocar en una bacteriemia (9) con una mortalidad anual considerable debido a la gran utilización de CVP 10 .…”
Section: Nº 45 Enero 2017unclassified
See 1 more Smart Citation
“…La flebitis asociada a los dispositivos venosos causa infección nosocomial, lo que puede suponer una prolongación de la estancia hospitalaria e incluso complicarse con una sepsis, aunque la incidencia es baja (10) . En la mayoría de los casos se trata de infección por Estafilococo Aureus que puede desembocar en una bacteriemia (9) con una mortalidad anual considerable debido a la gran utilización de CVP 10 .…”
Section: Nº 45 Enero 2017unclassified
“…En la mayoría de los casos se trata de infección por Estafilococo Aureus que puede desembocar en una bacteriemia (9) con una mortalidad anual considerable debido a la gran utilización de CVP 10 .…”
Section: Nº 45 Enero 2017unclassified
“…At best, these may be inconvenient and costly, and at worst they might actually be harming our patients. 2 The ED is therefore in the ideal position to prevent harm. 'Not doing stuff' is hard for an ED doctor -like the counter-intuitive nature of leaning out from the mountainside while skiing downhill.…”
Section: Doi: 101111/1742-672312109mentioning
confidence: 99%
“…A paper published recently by Stuart et al in the Medical Journal of Australia demonstrated that almost a quarter of healthcare-associated Staphylococcus aureus bacteraemias (SABs) were associated with PIVCs. 2 Almost 40% of these PIVCassociated SABs in this study were from i.v. cannulae inserted in the ED.…”
mentioning
confidence: 99%
See 1 more Smart Citation